Investigation of the Relationship Between Technology Addiction and Posture, Balance, and Muscle Strength in Preschool Children - Orunbayev, Agabek; Güneş, Musa; Yana, Metehan (Addicta: The Turkish Journal on Addictions, 2024)
Abstract: The aim of this study was to examine the relationship between technology addiction and posture, balance, and muscle strength in preschool children. Fifty-six children (26 boys and 30 girls) between the ages of 4 and 6 participated in this study. Technology addiction of the children participating in the study was evaluated with the Problematic Technology Use Scale for Young Children (PTUS-YC), muscle strength was evaluated with the Lafayette Manual Muscle Testing Device, balance was evaluated with the Y Balance Test, and posture was evaluated with the New York Posture Analysis. A moderate negative correlation was found between PTUS-YC and NYPA scores (r = −.540, p < .01). Additionally, a moderate negative correlation was found between PTUS-YC and the YBT (r = −.318, p < .017). When the relationship between PTUS-YC and muscle strength was examined, a moderate positive correlation was found between the right and left hip extensors and the left knee flexors (right: r = .318, p < .017; left hip: r = .381, p < .004; left knee: r = 0.324, p < .015). In conclusion, an increase in problematic technology use in preschool-aged children is associated with an increase in balance and posture disorders. Therefore, suggestions to reduce the level of problematic technology use may be effective in the development of balance and posture.
Keywords: addiction; balance; muscle strength; posture; preschool children